Precipitation and temperature shape the biogeography of arbuscular mycorrhizal fungi across the Brazilian Caatinga. (5th May 2022) - Sousa, Natália M. F.; Roy, Julien; Hempel, Stefan; Rillig, Matthias C.; Maia, Leonor C.
Abstract: Aim: Deterministic and neutral processes shape the biogeography of fungi. Arbuscular mycorrhizal fungi (AMF), an important group of plant root symbionts, remains poorly studied in the Neotropics. Here, we provided the first molecular survey of AMF diversity and tested whether the environment or space shapes AMF biogeography along a 12° latitudinal transect in the Brazilian Caatinga, a unique tropical dry forest ecoregion. Location: Caatinga, Brazil. Taxon: Arbuscular mycorrhizal fungi (Glomeromycotina). Methods: Soil and root samples were collected across a latitudinal transect of 1500 km within the Brazilian Caatinga. AMF communities were characterized using Illumina LSU amplicon sequencing. Operational taxonomic unit (OTU) richness, composition and phylogenetic niche conservatism were assessed using univariate and multivariate analyses, and the potential for new taxa discovery was assessed with BLAST analysis against reference and environmental sequences sets. Result: Glomeraceae was the most abundant and diverse family, resembling more dry Saharo‐Arabian and Australian realms or European croplands than other tropical forests from South America, but 10% of the OTUs could be taxa new to science, especially within Archaeospora, Claroideoglomus, Acaulospora, Gigaspora, Dentiscutata and Redeckera . AMF communities showed strong biogeographical structure inconsistent with a classical latitudinal diversity gradient, which further differed between soil and roots. Soil AMF biogeography best correlated with precipitation; community composition converged and richness increased towards both ends of the latitudinal transect where precipitation increased. Root AMF biogeography correlated to temperature, with decreasing diversity at higher temperatures. We found no evidence of phylogenetic niche conservatism. Main conclusions: Niche‐based processes driven by regional climate, most importantly precipitation and temperature, shape AMF biogeography across the Caatinga, with niche divergence among closely related AMF taxa. Given the expected future decrease in precipitation and increase in temperature, climate change may strongly affect the unique and yet unknown AMF biodiversity in neotropical dry forests.